Ross Procedure in Children: 17‐Year Experience at a Single Institution. Issue 2 (19th April 2013) - Tan Tanny, Sharman P.; Yong, Matthew S.; d'Udekem, Yves; Kowalski, Remi; Wheaton, Gavin; D'Orsogna, Luigi; Galati, John C.; Brizard, Christian P.; Konstantinov, Igor E.
Abstract : Background: The Ross procedure in children carries substantial mortality and reoperation rate. Aortic root dilatation is of concern. To prevent dilatation of the neoaortic root, but permit normal growth, we began to apply an absorbable poly‐( p ‐dioxanone)‐filaments (PDS) band at the sino‐tubular (ST)‐junction. Methods and Results: All children (n=100) who underwent Ross procedure during 1995–2012 were studied. Mean age at operation was 8.6±6.1 years (median 8.3 years, range 3 days to 18 years); 19 patients were younger than 1 year of age. The root replacement (n=91, Ross‐Konno procedure in 29 patients), root inclusion (n=6), and subcoronary implantation (n=3) techniques were used. Operative mortality was 6% (6/100, 4 neonates, 2 infants). Age of <1‐year at time of operation was a risk factor for early death ( P <0.001). Mean follow‐up time was 7.0±4.8 years (median 7.4 years, range 5 days to 16 years). Late mortality was 4.3% (4/94). Freedom from moderate or greater neoaortic valve insufficiency (AI) at 5 and 10 years was 89% and 83%, respectively. Freedom from neoaortic valve reoperation at 5 and 10 years was 96% and 86%, respectively. Aortic dilatation to Z‐score >4 was greatest at the ST‐junction (23%, 11/48) compared to the aortic annulus (17%, 11/66) and sinuses (14%, 7/50). Since 2001, a PDS band was placed around the ST‐junction in 19 patients. Survivors with the PDS band had less AI (0 versus 20%, P =0.043) compared to survivors (n=35) without the PDS at 4.1±3 years. Conclusions: The Ross procedure in children can be performed with acceptable results. Children younger than 1 year of age have higher mortality, but not an increased autograft reoperation rate. Stabilization of the ST‐junction may reduce AI.